Peran Badan Usaha Milik Desa (BUMDES) Dalam Pengelolaan Keuntungan Objek Wisata Di Desa Ekasari Kabupaten Jembrana - Ni Putu Ayu Diah Novianti; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2022)
The government strives to improve the community's economy, one of which is through Village-Owned Enterprises. Village-Owned Enterprises are institutions that were formed as an effort by the village government to improve the welfare of rural communities in accordance with their potential. Ekasari Village has tourism potential, the role of BUMDes is needed for its management. The purpose of this study was to analyze the management of tourism object profits by the Ekasari Village Owned Enterprise. The study was conducted using empirical methods and a sociological approach to law. The data used in this study are primary data and secondary data. Data were analyzed using qualitative descriptive methods. The results showed that BUMDes Ekasari made efforts related to regulating the development of tourism objects, namely by coordinating with tourism object managers so that they could be managed directly by the BUMDes Ekasari. Ekasari BUMDes profits are obtained through other business units, which will later be used for capital reserves, village income, and social funds. In addition, the role of the Village Government, Ekasari BUMDes to the community is very much needed in order to achieve the prosperity of the Village community through structured management of Ekasari BUMDes.